The Impact of EMI (English as Medium of Instruction) Translanguaging on Medical Students' Learning at Sebha University, Libya (Sebha University Conference Proceedings, 2025)
In the context of globalization, English as a Medium of Instruction (EMI) has become a common approach in higher education, especially in non-English-speaking countries. This study investigates the impact of translanguaging practices, utilizing students' native languages alongside English, on the learning experiences of medical students at Sebha University in Libya. It explores how these practices affect comprehension, retention, engagement, and academic performance in medical education. The research employs a qualitative case study approach, using semi-structured interviews, focus group discussions, and classroom observations to gather detailed insights from a diverse group of students at the Faculty of Medicine. Thematic analysis is used to identify patterns and themes within the collected data, illuminating the benefits and challenges of translanguaging in an EMI context. The findings indicate that translanguaging practices enhance students' understanding of complex medical concepts, foster engagement, and improve retention. However, institutional attitudes and policies significantly influence the successful implementation of these practices. This study underscores the necessity for inclusive educational strategies that respect linguistic diversity while optimizing EMI outcomes. Recommendations are provided to enhance translanguaging practices, aiming to improve the academic success and global competitiveness of medical students in multilingual environments.